The Effects of Covid19 Pandemic on Tourism Sector - Espinoza, Miguel CÃ³rdova; Nair, Rajesh Kumar; Mulani, Rafick; Kaakandikar, Rishikaysh; Quispe, Alexandra; Riva, Fiorella (International Journal of Tourism and Hospitality in Asia Pasific, 2021)
In this research, we are going to analyze the effects of Covid 19 pandemic on the human resources management in the tourism sector. MakeMyTrip is Indian online tourism company which provides online travel services, including flight tickets, domestic and international vacation packages, hotel reservations, railways and bus tickets. MakeMyTrip has branch office in New York, Singapore, Kuala Lumpur, Phuket, Bangkok, and Dubai.Â  This sector is one of the most affected by the pandemic. This study aims to analyze how employees adapt to the new needs of the sector and how companies motivate them to meet the organizational goals. The method used in this study was descriptive method in which the data taken from secondary source such as research articles and scientific journal. The results found that as many as 350 employees of MakeMyTrip had been laid off in order to maintain the company financial remain stable. They also reduce their variable costs such as advertising, sales promotions, payment gateway costs, optimized IT infrastructure and expenses related to the operation of their offices and other facilities.